2012
DOI: 10.1083/jcb.201111130
|View full text |Cite
|
Sign up to set email alerts
|

Agrin regulates CLASP2-mediated capture of microtubules at the neuromuscular junction synaptic membrane

Abstract: Agrin regulates acetylcholine receptors at the neuromuscular junction by locally stabilizing microtubules through the plus end tracking proteins CLASP2 and CLIP-170.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 51 publications
7
94
0
1
Order By: Relevance
“…LL5b, CLASPs and ELKS were also shown to concentrate at podosomes, actin-rich structures, which can remodel the extracellular matrix (Proszynski and Sanes, 2013). Interestingly, LL5b-containing podosome-like structures are also formed at neuromuscular junctions (Kishi et al, 2005;Proszynski et al, 2009;Proszynski and Sanes, 2013), and the complexes of LL5b and CLASPs were shown to capture microtubule plus ends and promote delivery of acetylcholine receptors (Basu et al, 2015(Basu et al, , 2014Schmidt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…LL5b, CLASPs and ELKS were also shown to concentrate at podosomes, actin-rich structures, which can remodel the extracellular matrix (Proszynski and Sanes, 2013). Interestingly, LL5b-containing podosome-like structures are also formed at neuromuscular junctions (Kishi et al, 2005;Proszynski et al, 2009;Proszynski and Sanes, 2013), and the complexes of LL5b and CLASPs were shown to capture microtubule plus ends and promote delivery of acetylcholine receptors (Basu et al, 2015(Basu et al, , 2014Schmidt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The CLASPs (CLASP1 and CLASP2), discovered in 2001 as binding partners for the CAP-Gly domain-containing linker proteins 1 and 2 (CLIP1/CLIP-170 and CLIP2/CLIP-115), were initially found to bind and stabilize the growing, distal ends of microtubules, independently of the CLIPs (17). Subsequent studies revealed that CLASPs localize wherever microtubules are needed, kinetochores in the nucleus for mitosis (18)(19)(20)(21)(22)(23), the cell cortex (24-27), the leading edge lamella and lamellipodium of motile cells (28)(29)(30)(31), the Golgi (17,(32)(33)(34)(35)(36)(37)(38), axons (39, 40), the developing apical membrane surface during lumen formation within endothelial cells (41), adherens junctions at cell-cell contacts (42, 43), the neuromuscular junction (44)(45)(46), podosomes (47), and focal adhesions (48). Within each of these molecular systems, the dynamic instability of microtubules undergo differential regulation by proteins specific to each of the biological processes (49)(50)(51)(52)(53)(54)(55).…”
Section: Introductionmentioning
confidence: 99%
“…CLIP1 was also shown to be involved in the maintenance of a normal neuromuscular phenotype. 26 The N-terminal region of CLIP1 interacts with EB1 and alphatubulin, leading to CLIP1 localization on MT plus ends. 27 CLIP1 also interacts with IQGAP1 (IQ Motif Containing GTPase Activating Protein 1), which together with CLIP1, is part of a complex that has a role in linking the actin cytoskeleton to MTs during cell migration.…”
Section: Discussionmentioning
confidence: 99%